The Hunger Games - Collins, Suzanne (New York : Scholastic Press, 2008)
Sixteen-year-old Katniss Everdeen accidentally becomes a contender in the annual Hunger Games, a grave competition hosted by the Capitol where young boys and girls are pitted against one another in a televised fight to the death.
Young Adult
Young Adult
Keywords: Contests -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Contests -- Fiction; Interpersonal relations -- Fiction; Science fiction; Survival -- Fiction; Television programs -- Fiction; Contests -- Fiction; Interpersonal relations -- Fiction; Science fiction; Survival skills -- Fiction; Television programs -- Fiction; Science fiction